School evaluation in Sweden in a local perspective: A synthesis. Issue 3 (1st January 2016) - Hanberger, Anders; Carlbaum, Sara; Hult, Agneta; Lindgren, Lena; Lundström, Ulf
Abstract : This article synthesises the role of evaluation at the municipal, school, classroom and parental levels of governance, and discusses the results of the articles appearing in this special issue. The discussion concerns the role of evaluation in school governance, the value of evaluation for local school development, the constitutive effects of evaluation, what explains the present results, how knowledge produced by evaluation can be used, and methodological issues. The results indicate that evaluation systems legitimise and support governance by objectives and results, parental school choice, and accountability for fairness and performance. Evaluation systems emphasise measurable aspects of curricula and foster a performance-oriented school culture. The most important evaluations for improving teaching and schools are teachers' own evaluations. The article suggests two explanations for the actual roles of evaluation in local school governance. First, both the governance structure and applied governance model delimit and partly shape the role of evaluation at local governance levels. Second, how local school actors use their discretion and interpret their role in the education system, including how they respond to accountability pressure, explains how their roles are realised and the fact that actors at the same level of governance can develop partly different roles.